Combined fibrinogen and neutrophil‐lymphocyte ratio as a prognostic marker of advanced esophageal squamous cell carcinoma. Issue 2 (February 2017) - Kijima, Takashi; Arigami, Takaaki; Uchikado, Yasuto; Uenosono, Yoshikazu; Kita, Yoshiaki; Owaki, Tetsuhiro; Mori, Shinichiro; Kurahara, Hiroshi; Kijima, Yuko; Okumura, Hiroshi; Maemura, Kosei; Ishigami, Sumiya; et al.
Abstract : Patients with advanced esophageal squamous cell carcinoma (ESCC) is received chemoradiotherapy or chemotherapy for clinical management. However, it is difficult to predict tumor response and prognosis using blood markers before starting treatments. The purpose of this study was to investigate the pre‐treatment plasma fibrinogen and neutrophil–lymphocyte ratio (NLR) in patients with advanced ESCC treated with chemoradiotherapy or chemotherapy, and to assess the clinical utility of a combined score using these blood markers, named as the F‐NLR (fibrinogen and NLR) score, as a predictor of tumor response and prognosis. A total of 98 advanced ESCC patients, treated with chemoradiotherapy or chemotherapy, were classified into three groups: F‐NLR score of 2, having both hyperfibrinogenemia (>400 mg/dL) and high NLR (>3.0), score of 1, one of these hematological abnormalities, and score of 0, having neither hyperfibrinogenemia nor high NLR. Fibrinogen and NLR were significantly higher in the progressive disease (PD) group than the non‐PD group ( P =  0.0419, and P =  0.0001, respectively). A significantly higher F‐NLR score was found in the PD group than the non‐PD group ( P =  0.0140). Overall survival was significantly lower in patients with an F‐NLR score of 2 than in those with an F‐NLR score of 0 or 1 ( P <  0.0001). Multivariate analysis showed that the F‐NLR score was one of the independent prognostic factors ( P =  0.0081). Our study demonstrates that the F‐NLR score is promising as a predictive marker for therapeutic effects and prognosis in patients with advanced ESCC. Abstract : We demonstrated that the combined score for both plasma fibrinogen and neutrophil‐lymphocyte ratio (named as the F‐NLR score) is a promising blood marker for predicting therapeutic effects and prognosis in patients with advanced esophageal squamous cell carcinoma. The F‐NLR score may serve as an economical biomarker for determining the therapeutic plan in patients with advanced esophageal squamous cell carcinoma.